Proteins - Walker, John M.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 1984)
In recent years there has been a tremendous increase in our understanding of the functioning of the cell at the molecular level. This has been achieved in the main by the invention and development of new methodology, parti- larly in that area generally referred to as "'genetic en- neering". While this revolution has been taking place in the field of nucleic acids research, the protein chemist has at the same time developed fresh methodology to keep pace with the requirements of present day molecular bi- ogy. Today's molecular biologist can no longer be content with being an expert in one particular area alone. He/she needs to be equally competent in the laboratory at h- dling DNA, RNA, and proteins, moving from one area to another as required by the problem he/she is trying to solve. Although many of the new techniques in molecular biology are relatively easy to master, it is often difficult for a researcher to obtain all the relevant information nec- sary for setting up and successfully applying a new te- nique. Information is of course available in the research l- erature, but this often lacks the depth of description that the new user requires. This requirement for in-depth pr- tical details has become apparent by the considerable - mand for places on our Molecular Biology Workshops held at Hatfield each summer.
The Lowry Method for Protein Quantitation -- Determination of Protein Molecular Weights by Gel Permeation High Pressure Liquid Chromatography -- Immunoaffinity Purification of Protein Antigens -- Electrophoretic and Chromatographic Separation of Peptides on Paper -- Peptide Mapping by Reverse-Phase High Pressure Liquid Chromatography -- SDS Polyacrylamide Gel Electrophoresis of Proteins -- Gradient SDS Polyacrylamide Gel Electrophoresis -- Acetic Acid-Urea Polyacrylamide Gel Electrophoresis of Proteins -- The In Vivo Isotopic Labeling of Proteins for Polyacrylamide Gel Electrophoresis -- Two-Dimensional Polyacrylamide Gel Electrophoresis of Proteins -- Starch Gel Electrophoresis of Proteins -- Isoelectric Focusing in Ultrathin Polyacrylamide Gels -- High-Sensitivity Silver Staining of Proteins Following Polyacrylamide Gel Electrophoresis -- Quantification of Proteins on Polyacrylamide Gels (Nonradioactive) -- Computer Analysis of Gel Scans -- Drying Gels -- Fluorography of Polyacrylamide Gels Containing Tritium -- Recovery of Proteins from Dried Polyacrylamide Gels after Fluorography -- The Electrophoretic Elution of Proteins from Polyacrylamide Gels -- Transfer Techniques in Protein Blotting -- Peptide Mapping by Thin-Layer Chromatography and High Voltage Electrophoresis -- In Situ Peptide Mapping of Proteins Following Polyacrylamide Gel Electrophoresis -- The Dansyl Method for Identifying N-Terminal Amino Acids -- The Dansyl-Edman Method for Peptide Sequencing -- Microsequencing of Peptides and Proteins with 4-N,N-Dimethylaminoazobenzene-4?-isothiocyanate -- Manual Edman Degradation of Proteins and Peptides -- Carboxyl-Terminal Sequence Determination of Proteins and Peptides with Carboxypeptidase Y -- Immunization and Fusion Protocols for Hybridoma Production -- Immunofluorescence and Immunoperoxidase Screening of Hybridomas -- Solid-Phase Screening of Monoclonal Antibodies -- Subclass Analysis and Purification of Monoclonal Antibodies -- The Production of Antisera -- Immunodiffusion in Gels -- Crossed Immunoelectrophoresis -- Rocket Immunoelectrophoresis -- Radioiodination of Proteins -- Radioimmunoassay -- Enzyme-Linked Immunosorbant Assay (ELISA).
Keywords: Biochemistry; Biochemistry, general